2014
DOI: 10.1186/1423-0127-21-2
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial progesterone resistance and PCOS

Abstract: Polycystic ovary syndrome (PCOS) is a state of altered steroid hormone production and activity. Chronic estrogen exposure or lack of progesterone due to ovarian dysfunction can result in endometrial hyperplasia and carcinoma. A key contributor to our understanding of progesterone as a critical regulator for normal uterine function has been the elucidation of progesterone receptor (PR) expression, regulation, and signaling pathways. Several human studies indicate that PR-mediated signaling pathways in the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 55 publications
(103 reference statements)
3
94
1
1
Order By: Relevance
“…The fact that some outcomes were worsened in hyperandrogenic PCOS phenotypes may relate to the reciprocal relationship between HA and IR (either intrinsic or extrinsic related to obesity) 4,107 in PCOS. This likely aggravates sex hormone imbalances that contribute to adverse pregnancy and birth outcomes through endometrial abnormalities like thickening the endometrium, 108 dysregulating angiogenesis, 92 and inducing a state of inflammation in endometrium 94,[109][110][111] and consequently impacting on implantation and placentation. 25,92,108 The prevalence of outcomes did not significantly change on exclusion of studies using metformin during pregnancy, which is consistent with prior literature on miscarriage, 112 GDM, 113 and PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that some outcomes were worsened in hyperandrogenic PCOS phenotypes may relate to the reciprocal relationship between HA and IR (either intrinsic or extrinsic related to obesity) 4,107 in PCOS. This likely aggravates sex hormone imbalances that contribute to adverse pregnancy and birth outcomes through endometrial abnormalities like thickening the endometrium, 108 dysregulating angiogenesis, 92 and inducing a state of inflammation in endometrium 94,[109][110][111] and consequently impacting on implantation and placentation. 25,92,108 The prevalence of outcomes did not significantly change on exclusion of studies using metformin during pregnancy, which is consistent with prior literature on miscarriage, 112 GDM, 113 and PE.…”
Section: Discussionmentioning
confidence: 99%
“…This likely aggravates sex hormone imbalances that contribute to adverse pregnancy and birth outcomes through endometrial abnormalities like thickening the endometrium, 108 dysregulating angiogenesis, 92 and inducing a state of inflammation in endometrium 94,[109][110][111] and consequently impacting on implantation and placentation. 25,92,108 The prevalence of outcomes did not significantly change on exclusion of studies using metformin during pregnancy, which is consistent with prior literature on miscarriage, 112 GDM, 113 and PE. 114 With regard to study quality, higher miscarriage, GDM, GHTN, PE, and CS were confirmed on good quality studies with the lowest risk of bias, validating the observed results on these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Even though progesterone-based oral contraceptive therapy is often eicacious [19], approximately 30% of women with PCOS fail to respond to such treatment [20] and progress to the development of atypical hyperplasia and further transformation to endometrial cancer [21].…”
Section: Prevention Of Endometrial Hyperplasiamentioning
confidence: 99%
“…Patients with PCOS have a modiied ratio of PRA to PRB receptors present on stromal and epithelial cells of endometrium [21].…”
Section: Prevention Of Endometrial Hyperplasiamentioning
confidence: 99%
“…They suggested that the decrease in cell apoptosis during the implantation window in PCOS patients may be one of the causes of reduced endometrial receptivity. Finally, a recent review of endometrial progesterone resistance in women with PCOS concluded that progesterone-mediated signaling pathways of expression, regulation and signaling in the nucleus are involved [23].…”
Section: Accepted Manuscriptmentioning
confidence: 99%